RECENT TRENDS & APPLICATIONS IN HRV - Malarvili Balakrishnan, editor; Heemahlatha Manoharan, contributor; I. N. Fariza, contributor; Kamarulafizam Ismail, contributor; Mahyar Hamedi, 1983-, contributor; Malarvili Balakrishnan, contributor; Maya Abdullah Maamuom, contributor; Noor Aimie Salleh, contributor; Om Prakash Singh, contributor; Sheikh Hussain Shaikh Salleh, 1958-, contributor; Hairi Zamzuri, contributor; Mohd. Azizi Abdul Rahman, contributor; et al. (Johor Bahru, Johor : PENERBIT UTM PRESS, 2016)
Includes bibliographical references and index